Structural analysis of leucine, lysine and tryptophan mitochondrial tRNA of nesting turtles Caretta caretta (Testudines: Chelonioidea) in the Colombian Caribbean (2020)
The understanding of the functional properties of mitochondrial transfer RNA (mt tRNAs) depend on the knowledge of its structure. tRNA acts as an interface between polynucleotides and polypeptides thus, they are key molecules in protein biosynthesis. The tRNA molecule has a functional design and, given its importance in the translation of mitochondrial genes, it is plausible that modifications of the structure can affect the synthesis of proteins and the functional properties of the mitochondria. In a previous work, the mitochondrial genome of an individual of the nesting Caretta caretta of the Colombian Caribbean was obtained, where specific mutations were identified in the only tRNALeu (CUN), tRNATrp and tRNALys genes. In order to analyze the effect of these mutations on these three mt tRNAs, the prediction of 2D and 3D structures was performed. Genes were sequenced in 11 nesting loggerhead turtles from the Colombian Caribbean. Two-dimensional structures were inferred using the ARWEN program, and three-dimensional structures were obtained with the RNA Composer 3D program. Two polymorphisms were identified in tRNATrp and another one was located in tRNALys, both specific to C. caretta. The thymine substitution in nucleotide position 14 of tRNATrp could constitute an endemic polymorphism of the nesting colony of the Colombian Caribbean. Two 2D and three 3D patterns were obtained for tRNATrp. In the case of tRNALys and tRNALeu 2D and 3D structures were obtained respectively, which showed compliance to canonical structures, with 4 bp in the D-arm, 4-5 bp in the T-arm, and 5 bp in the anticodon arm. Moderate deviations were found, such as a change in the number of nucleotides, elongation in loops or stems and non-Watson-Crick base pairing: adenine-adenine in stem D of tRNATrp, uracil-uracil and adenine-cytosine in the acceptor arm of the tRNALys and cytosine-cytosine in the anticodon stem of the tRNALeu. In addition, distortions or lack of typical interactions in 3D structures gave them unique characteristics. According to the size of the variable region (4-5 nt), the three analyzed tRNAs belong to class I. The interactions in the three studied tRNAs occur mainly between D loop-variable region, and between spacer bases-variable region, which classifies them as tRNA of typology II. The polymorphisms and structural changes described can, apparently, be post-transcriptionally stabilized. It will be crucial to perform studies at the population and functional levels to elucidate the synthetic pathways affected by these genes. This article analyses for the first time the 1D, 2D and 3D structures of the mitochondrial tRNALys, tRNATrp and tRNALeu in the loggerhead turtle.